2016
DOI: 10.1021/acs.iecr.6b01424
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Foam Transport from a Texture-Implicit Local-Equilibrium Model with an Improved Parameter Estimation Algorithm

Abstract: We present an insightful discussion on the implications of foam transport inside porous media based on an improved algorithm for the estimation of model parameters. A widely used texture-implicit local-equilibrium foam model, STARS TM , is used to describe the reduction of gas mobility in the state of foam with respect to free gas. Both the dry-out effect and sheardependent rheology are considered in foam simulations. We estimate the limiting capillary pressure ! * from values in the STARS TM model to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 65 publications
(151 reference statements)
1
54
0
2
Order By: Relevance
“…They concluded that, presence of oil has less destabilizing effect on foams in the low foam-quality regime compared to the foams in the high foam-quality regime. Similar phenomena have been described in (Batôt et al 2016;Zeng et al 2016).…”
Section: Properties Of Eor-foamsupporting
confidence: 86%
“…They concluded that, presence of oil has less destabilizing effect on foams in the low foam-quality regime compared to the foams in the high foam-quality regime. Similar phenomena have been described in (Batôt et al 2016;Zeng et al 2016).…”
Section: Properties Of Eor-foamsupporting
confidence: 86%
“…The shear-thinning function F 4 is defined as g /(ΦS g ) the interstitial foamedgas velocities, σ the surface tension between gas and water in presence of surfactant and e c the shear-thinning exponent. The F 4 function definition remains controversial since some authors [30,31,32] consider the total velocity instead of the gas velociy to define the capillary number.…”
Section: Implicit-texture Foam Modelmentioning
confidence: 99%
“…Later on, Ma et al [20] determined the same three model parameters (M ref , S * -SE w , Θ ) by using a least squares minimization method as other authors, but adding a constraint on S * -SE w to avoid non unique (M ref , S * -SE w ) solutions. Then, Zeng et al [38] converted the three-parameter (M ref , S * -SE w , Θ ) optimization problem (Ma et al [20]) to a single-parameter (M ref ) problem by using steady state apparent viscosity data and searching the M ref value that fits a linear function of the saturation with (S * -SE w , Θ ) as parameters. The same authors also adjusted the shear-thinning function separately from total-flow-rate-scan experiments.…”
Section: Comparison With Other Calibration Methodsmentioning
confidence: 99%